Analisis Kesiapan Obat Dalam Penegakan Diagnosa Wajib BPJS di Puskesmas Busalangga, Kabupaten Rote Ndao-Nusa Tenggara Timur - Irene Marilyn Bentura, Maulita Indrisari Fajriansyah, Rahmad Aksa (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Healthcare and Sosial Security Agency (BPJS Kesehatan) is a law agency set up to organize the health insurance program operates since 1 January 2014. Health center as the first-level health care provide BPJS Kesehatan service in JKN/BPJS system has a major task in public health services. This study aimed to determine the amount of drugs availability in Busalangga health center to enforce 144 BPJS diagnosis. The LPLPO parameter was used to see the availability of drugs base on National Formulary (FORNAS) 2014 as standard reference. The result showed that drugs availability in Busalangga health center was 31,96 %. Which is compared with National Formulary there 68,04 % of drugs were not yet available to enforce BPJS 144 diagnosis. Based on these result, it can be concluded that drugs availability in Busalangga health center does not meet the standard in National Formulary 2014. Research suggest that the planning and procurement of drugs at Busalangga health center should refer to National Formulary as standard reference of treatment in 144 basic diagnosis enforcement independently and completely at the Busalangga health center.